Atrial fibrillation in The Tromsø Study 1994-2007. Risk factors, occurrence and gender differences. - Nyrnes, Audhild (UiT The Arctic University of Norway, 2016)
Paper I and III are not available in Munin: Paper I. Palpitations are predictive of future atrial fibrillation. An 11-year follow-up of 22,815 men and women: the Tromsø Study. Nyrnes A. et al. Available in European Journal of Preventive Cardiology, 2013 Oct;20(5):729-36 Paper III. Uric acid is associated with future atrial fibrillation: an 11-year follow-up of 6308 men and women--the Tromso Study. Nyrnes A. et al. Available in Europace. 2014 Mar;16(3):320-6 Summary Atrial fibrillation (AF) is a common cardiac arrhythmia, which increases morbidity and mortality and thereby imposes high health costs on society. The prevalence of AF has increased for several decades, and is expected to increase further, with the rising numbers of elderly people and survivors of heart diseases. Several risk factors for AF related to genetics and diseases have been established. Focus is now also set on novel risk factors related to symptoms, life style and inflammation. The identification of risk factors is important, as some of them could be modifiable. The population-based Tromsø Study made it possible to follow survey participants from the fourth survey in 1994, who were free of AF at baseline, to study different risk factors for AF and the impact of these. We also wanted to investigate the frequency of AF in our population. All research questions were analysed with a gender perspective. We were able to follow nearly 23 000 persons for a mean of 11 years, and found that 2.2% of women and 3.3% of men in this population were diagnosed with AF. A main new finding was the importance of self-reported palpitations as a risk factor for AF. The association was stronger in men than in women. We also found different strength of associations in women and men for several other variables. Coronary heart disease and overweight were stronger risk factors in men. Hypertension was a stronger risk factor in women, and diabetes predicted AF in women only. A limited number of inflammatory biomarkers were available for this study. We found that ...